Thematic Analysis of Doctoral Theses Awarded in Library and Information Science: A Comparative Study of All India Level with Panjab University, Chandigarh: 1950-2017 - Verma, Reshma Rana; Kumar, Shiv (DESIDOC Journal of Library & Information Technology, 2025)
The study examines 3011 doctoral theses awarded at national level in the discipline of “Library and Information Science” and 62 doctoral theses awarded between 1950-2017 at the “Department of Library & Information Science, Panjab University, Chandigarh”. The analysis is based on the thematic classification of the doctoral theses. At the All-India level, theses have been classified into 68 themes while the 62 doctoral theses awarded by Panjab University are classified into 25 themes, with varying numbers per theme. The decade wise growth of doctoral thesis submitted at “Panjab University, Chandigarh” has been discussed to see the growth over the years. The literature review has made it evident that more focus is on the themes like Library use and user studies and Information and Communication Technology. In the present study, themes that have been arranged in rank and order are also discussed to draw a comparative view of national level themes with the “Panjab University, Chandigarh”. The study also aims to present the similarities and dissimilarities of the doctoral research theses objectively based on their themes.